Actitud de la gestante durante el trabajo de parto después de la aplicación de un programa de Psicoprofilaxis Obstétrica en el hospital II Essalud•Tarapoto. Mayo 2012 • Abril 2013 - Galoc Chasquibol, Alis (2013)
The present study aimed to determine the attitude of the mother during labor after the implementation of a program of Psicoprofilaxis Obstetric Hospital II Essalud - Tarapoto. May 2012 - April 2013, for which a study of quantitative, descriptive, observational retro prospective, applied to 100 pregnant women who received obstetric Psicoprofilaxis program to collect data used card history and perinatal, collecting affiliation data of patients and the method' of data collection will be through evaluation form consisting of 20 questions which are divided by the three stage of labor . Expansion Period : 8 questions , second stage : 9 questions and Childbirth Period :3 questions . They were filled by obstetricians who provided care, since they me in direct contact: with patients, the evaluation will be measured according to the following parameters: Unfavourable: 1-50 and favorable: > 50-100. As a result of the investigation it was found that most women have had a favorable approach to expansion period of labor linked mainly to uterine contractions which -.les between 91-100% of the criteria responded favorably, and also evidenced that most women have had a favorable attitude against expulsive period of labor linked mainly uterine contractions which varies between 61-92% of the criteria responded favorably, and finally we realized that most women have had a favorable approach to delivery period of labor linked mainly to uterine contractions which varies between 92-100% of the criteria responded favorably. In conclusion, the study shows that 100% of the mothers had a psycho-prophylactic preparation. Therefore Psicoprofilaxis program contributed greatly to improve the include of the mother during the three periods of delivery.